The Problem Posing Ability of Student in Class IX on Cylinder Using Oil Context - Dhea Pratiwi; Zulkardi Zulkardi (SJME (Supremum Journal of Mathematics Education), 2026)
This study aims to describe the problem-posing abilities of ninth-grade students on the topic of cylinders using an oil context. A descriptive qualitative approach was conducted at SMP Negeri 10 Prabumulih with three students representing high, medium, and low academic levels. Data were collected through a problem-posing test and interviews, analyzed using data collection, reduction, presentation, and conclusion drawing techniques. The results showed that students’ problem-posing abilities varied across ability levels. High-ability students demonstrated flexibility in generating problems, used logical strategies, and drew conclusions relevant to the context. Medium-ability students were able to create new problems but still relied on familiar examples, while low-ability students experienced difficulties in formulating problems and performing calculations accurately. Indicators such as flexibility, originality, strategy use, argument analysis, and conclusion drawing were found to be interconnected. The use of the oil context increased students’ motivation because it was close to their daily experiences. However, real-life contexts alone did not ensure originality without teacher guidance. This study recommends integrating local contexts into problem-posing instruction to enhance students’ creativity, numeracy skills, and higher-order thinking abilities.